ممارسة العرائض الترابية على المستوى المحلي بالمغرب: دراسة سوسيوقانونية - سيح، رشيد; زكروم، سومية (المركز المغربي للدراسات الاستراتيجية والعلاقات الدولية, 2024)
تروم هذه الدراسة إلى تقديم قراءة سوسيوقانونية وفق مقاربة تحليلية لتجربة المغرب في مجال تفعيل ورش الديمقراطية التشاركية، وذلك عبر استقراء المتن التشريعي المتمثل في فصول الدستور والقانون التنظيمي المتعلق بالحق في تقديم العرائض إلى السلطات العمومية وبنود القوانين التنظيمية الخاصة بالجماعات الترابية بمستوياتها الثلاث (الجهات، العمالات والأقاليم، الجماعات)، والقوانين العادية ومختلف المراسيم التطبيقية والتي نصت أو أحالت على آليات وهيئات وكيفيات وشروط تفعيل الديمقراطية التشاركية ترابيا، ومقارنتها مع ما تحقق على أرض الواقع نتاج الممارسة لعقد ونيف من الزمن في التدبير التشاركي للشأن العام المحلي، مع الوقوف على أهم العوائق القانونية والمجتمعية التي تحول والتفعيل الأمثل لهذه الآلية المستجدة. بالإضافة إلى جرد "المنجز التشاركي" وتحليله على ضوء السياق الوطني، ومحاولة اقتراح بدائل لتجاوز الاختلالات المسجلة في أفق المساهمة في تعزيز وتنويع سبل وممكنات المشاركة المواطنة الفعالة والمسؤولة بما يتماشى والأهداف المرجوة من وراء لجوء المشرع الدسترة هذا المقتضى بين دفتي الوثيقة الدستورية الأخيرة للمملكة الصادرة بتاريخ 29 يوليو 2011. This study aims to provide a socio-legal analysis of Morocco's experience in activating participatory democracy. This is done by examining legislative texts, including constitutional provisions, organizational laws related to the right to submit grievances to public authorities, and specific regulations for local government units at all three levels (regions, provinces, and municipalities). The study also explores ordinary laws, various implementing decrees, and their provisions concerning the mechanisms, bodies, procedures, and conditions for activating territorial participatory democracy. The analysis involves comparing the legal framework and the practical implementation of participatory governance over a significant period in the management of local public affairs. The study identifies critical legal and societal obstacles that hinder the optimal implementation of this new mechanism. Additionally, it conducts an inventory of the "participatory achievements" and analyzes them in the context of the national landscape. The aim is to propose alternatives to overcome the observed imbalances, contributing to enhancing and diversifying avenues for effective and responsible citizen participation. This aligns with the objectives sought by the legislator in incorporating this provision into the recent constitutional document issued on July 29, 2011.
Keywords: العرائض الترابية -- المشاركة الوطنية -- المغرب